CRISPR-Associated Factor Csa3b Regulates CRISPR Adaptation and Cmr-Mediated RNA Interference in Sulfolobus islandicus - Ye, Qing; Zhao, Xueqiao; Liu, Jilin; Zeng, Zhifeng; Zhang, Zhufeng; Liu, Tao; Li, Yingjun; Han, Wenyuan; Peng, Nan (Frontiers in Microbiology, 2020)
Acquisition of spacers confers the CRISPR–Cas system with the memory to defend against invading mobile genetic elements. We previously reported that the CRISPR-associated factor Csa3a triggers CRISPR adaptation in Sulfolobus islandicus. However, a feedback regulation of CRISPR adaptation remains unclear. Here we show that another CRISPR-associated factor, Csa3b, binds a cyclic oligoadenylate (cOA) analog (5′-CAAAA-3′) and mutation at its CARF domain, which reduces the binding affinity. Csa3b also binds the promoter of adaptation cas genes, and the cOA analog enhances their binding probably by allosteric regulation. Deletion of the csa3b gene triggers spacer acquisition from both plasmid and viral DNAs, indicating that Csa3b acted as a repressor for CRISPR adaptation. Moreover, we also find that Csa3b activates the expression of subtype cmr-α and cmr-β genes according to transcriptome data and demonstrate that Csa3b binds the promoters of cmr genes. The deletion of the csa3b gene reduces Cmr-mediated RNA interference activity, indicating that Csa3b acts as a transcriptional activator for Cmr-mediated RNA interference. In summary, our findings reveal a novel pathway for the regulation of CRISPR adaptation and CRISPR–Cmr RNA interference in S. islandicus. Our results also suggest a feedback repression of CRIPSR adaptation by the Csa3b factor and the cOA signal produced by the Cmr complex at the CRISPR interference stage.